ANALISIS BENTUK DAN STRUKTUR KOMPOSISI â€œMORNING HAPPINESSâ€ GUS TEJA - Ariesta, I Made Jacky; Ardini, Ni Wayan; Darmayuda, I Komang; Sumerjana, Ketut (Institut Seni Indonesia Denpasar, 2018)
Gus Teja World Music?s musical composition